Should PLCs diversify into related or unrelated industries? Evidence from Malaysia - Mehmood, Khawaja Khalid; Abdullah, Haim Hilman (Mediterranean Center of Social and Educational Research (MCSER), 2015)
The primary issue in diversification strategy is concerning its type.A large body of research on the relative effect of related versus unrelated diversification still remains inconclusive. Scholars have been studying this topic through different research designs and in different contexts, although a greater part of the research was conducted in western economies.Importantly, certain scholars have asserted that powerful conclusions could be produced if product diversification is measured using powerful techniques and performance is assessed through combination of objective and subjective measures. This research builds up on that suggestion and revisits the subject using a sample of Malaysian PLCs as Malaysia has always been characterised by proliferation of diversified companies. This is also imperative keeping in view the challenges confronted by Malaysian economy in recent years and the significant repercussions of selecting type of diversification by Malaysian corporate sector.This study was conducted for multi-business PLCs listed on Main Market of Bursa Malaysia.T-tests based on 123 diversified PLCs revealed that related diversifiers outperformed unrelated diversifiers on Tobin’s q and price/book value. The study carries significant theoretical implications along with practical implications for Malaysian corporate sector and other PLCs facing similar business scenarios as in Malaysia.